Private radio stations fare better: audience perception of adherence to social responsibilities by public and private radio stations in Oyo State, Nigeria (2019)
Media Ownership factor in Nigeria, as the case in many countries, plays a significant role in determining the extent to which the audience perceive media organizations as being socially responsible especially as they service the democratic system. Existing studies have focused on the role of ownership generally in the media industry in Nigeria. However, such studies have given little attention to how public and private radio stations have fared in their social responsibilities to the public. Therefore, with the specific focus on Oyo State, which is one of the states with the highest concentration of radio stations in Nigeria, this study was designed to comparatively examine how public and private radio stations in the State fare in the performance of their expected social responsibilities. This study adopted the Social Responsibility Theory and combined Content Analysis and Survey as research methods. Content analysis revealed that the programme contents of the selected radio stations fairly meet up with the social responsibilities expected of the mass media as there are more of non-sponsored programmes than sponsored programmes in the stations’ programme schedules.